Proteção de ovinos e bovinos contra haemonchose após imunização com antígenos oriundos da membrana intestinal de Haemonchus contortus - Bassetto, César Cristiano [UNESP] (2015)
Probably the blood sucking nematodes of Haemonchus genus are the most economically important parasites in ruminants raised in warm damp climates of tropics and sub tropics. Due to the emergence of parasite populations with anthelmintic resistance, new alternatives for the control of gastrointestinal nematodes infections are being evaluated. A promising alternative due to its safety, are the vaccines. Several vaccines have been aimed using excretory/secretory antigens and the called hidden antigens. The vaccine with more efficacy is produced with gut membrane proteins from Haemonchus contortus. In the studies described here this vaccine was evaluated in three groups of sheep and cattle, one group was vaccinated with 5 μg and another with 50 μg of the antigen and the last group received only the adjuvant QuilA. Sheep received six shots 21 days apart, while calves received initially three shots three weeks apart and then four more times at six weeks intervals. The efficacy of the vaccine was similar in both doses (5 μg and 50 μg of antigen), in either sheep or cattle. Vaccination of calves induced high production of circulating antibody and consequent reduction in the egg output of Haemonchus spp.. Haemonchus placei and Haemonchus similis worm burden was reduced when compared with control group. Antibody titres from vaccinated ewes were relatively low and did not confer significant protection throughout the trial. In contrast, the antibody titres from vaccinated lambs were higher and caused significant reduction in the overall mean faecal egg counts and worm burden of H. contortus in comparison with the control group. Vaccination with intestinal membrane glycoproteins from H. contortus substantially reduce the infection for H. placei and H. similis in cattle. The vaccine also protected lambs against H. contortus infection, but did not protected ewes during the periparturient period